Incidencia del cumplimiento de tareas escolares en el bajo rendimiento de los alumnos del octavo año de educación básica del Colegio Técnico Dr. Demetrio Aguilera Malta del cantón Santa Rosa, período lectivo 2010-2011. - Allauca Vera, Verónica del Rocío (2011)
The matic of investigation that takes for title Incedence of the execution of the School Tasks in the first Floor Yield of the students of the 8vo year of basic Education of the Technical National School Demetrio Aerie Malt Of The canton Saint Rose Of The County Of The Gold in the period lectivo 2010-2011.